SOFTWARE “Prolit-lC” FOR MODELING OF FOUNDRY PROCESSES ON CLUSTERED MULTIPROCESSING TECHNOLOGIES OF SUPERCOMPUTER SKIF - A. N. Chiehko; V. F. Sobolev; O. I. Chiehko; S. G. Lihouzov (Литьë и металлургия)
The computer system “Prolit-lC”, intended for modeling of the casting molds filling process, in which cluster technologies of super-computer SKIF calculations are situated, is considered. The possibilities of software “Prolit-lC” are illustrated at the example of the industrial castings, produced in foundry.